Determination of pillar width to improve mining safety in a deep burst-prone coal mine. (March 2019) - Li, Xuwei; Chai, Yanjiang
Highlights: The influence of pillar width on roadway deformation was analyzed quantitatively. The pillar width was divided into four categories for the purpose of burst control. The applicability of different coal pillars was analyzed for deep burst-prone mines. Abstract: Coal burst is the main threat to coal mining safety in China. Coal pillars of appropriate width play a significant role in controlling stress distribution and coal burst hazard. In the latest National Coal Safety Standard (China), a qualitative principle is given for coal pillar design in burst-prone coal mines. However, specific and quantitative regulations on coal pillar design are more desirable in practice. In this study, the influence of a width-decreasing coal pillar on roadway convergence in a deep coal mine was investigated by numerical simulation and field measurement, which provides both qualitative and quantitative guidance on safe pillar design. Results and analysis indicate that: (1) The mining-induced width-deceasing coal pillar successively experienced the Fully Stable Coal Pillar (FSCP) stage, the Partially Stable Coal Pillar (PSCP) stage, the Critical Coal Pillar (CCP) stage and the Yielding Coal Pillar (YCP) stage; (2) The demarcation points of these four stages were approximately 100 m, 40 m and 10 m in a deep coal mine; (3) The priority in barrier pillar design should be given to YCP, FSCP and PSCP in sequence; (4) The priority in stop-line pillar design should be given to FSCP, followed by PSCP on condition that the roof strata in the stop-line area are fractured and de-stressed in advance; (5) CCP should be avoided in both the barrier pillar design and the stop-line pillar design in all circumstances. The above principles of coal pillar design can be used to improve mining safety in deep burst-prone coal mines of similar conditions.